Estilo atribucional frente a la interacción social de niños en el aula. - Navarro Roldan , Claudia Patricia (2022)
These papers sample the attribution style of children of 9 to 12 years as opposed to the social interactions in the class classroom. The Questionnaire of Social Interactions in the Classroom was designed and valued, and soon it is applied to 371 participants in 35 schools. A style of attribution in its dimensions predominates internal, stable and controllable, with tendency of social motivational dominion. Significant difference between the nature of the school (public vs. private) and internal and external styles. Significant difference between the motivational dominions of success in the dimension control-not, control and  gender. Also on the social Motivational Dominion in the dimension control-not control and gender